Fruit juices as carrier matrices of potentially probiotic bacteria - Fonseca, Hugo Calixto (2021)
Fermentation by probiotic lactic acid bacteria is recognized for its potential health benefits. Most probiotic products on the market are derived from milk, but there is a growing demand for plant-based probiotic foods. However, as several parameters influence the fermentation process, the correct choices of the type of substrate and the strain are paramount in the success of obtaining a final product with desirable characteristics. Thus, the first objective of this study was to evaluate the probiotic properties of 19 lactic acid bacteria belonging to the Agricultural Microbiology Culture Collection (CCMA) using resistance, safety and functionality tests, defining the strain with greater probiotic potential. Lactiplantibacillus plantarum CCMA 0743 had a high survival rate in simulated gastric and intestinal juices and exhibited greater hydrophobicity (96.06%). In the simulated competition and exclusion assays, strain CCMA 0743 was able to reduce the adhesion of Salmonella in both cell models (Caco-2 and HT-29) and the adhesion of Escherichia coli to HT-29 cells in the competition assay. In the second part, the phytochemical changes of the juices of acerola, sour coconut and passion fruit were evaluated by simple and mixed cultures of L. plantarum CCMA 0743 and Lacticaseibacillus paracasei LBC-81 at 37 °C/24 h to define the best fermentative matrix. After 18 h of fermentation, the passion fruit juice showed greater viability of the culture of L. plantarum CCMA 0743 single or mixed, above 9.00 Log CFU/mL and pH between 4.07-4.10. Sugar’s consumption and organic acid production were influenced by the substrate and the culture used. The fermentative process reduced the antioxidant activity and the carotenoid content. However, the isolated culture of L. plantarum CCMA 0743 increased the content of yellow flavonoids in the passion fruit juice. Finally, the study investigated the effect of Lactobacillus strains on profiles of volatile compounds and sensory of passion fruit juice. Finally, the viability of the strains was evaluated under simulated gastrointestinal conditions and refrigerated storage of the product. L. plantarum CCMA 0743 showed high viability (6.18 Log CFU/mL) in the final stage of the simulated digestion of passion fruit juice. Both juices, single or mixed fermentation, maintained adequate counts (> 8.0 Log CFU/mL) during storage and the yellow color was stable for 28 days. The sensory profile of passion fruit juice was modified by simple and mixed fermentations. According to the results obtained, L. plantarum CCMA 0743 proved to be an excellent candidate for use as a probiotic, showed high cell viability and increased bioactive compounds in passion fruit juice. In general, passion fruit juice proved to be an adequate food matrix for fermentation of the studied strains and production of a drink with desirable physicochemical, microbiological, and sensory characteristics.